Supplementation of DHA enhances the cryopreservation of yak semen via alleviating oxidative stress and inhibiting apoptosis - Zhu, Yanjin; Yu, Jun; Li, Xupeng; Chen, Zhuo; Li, Yuan; Xiong, Yan; He, Honghong; Yin, Shi; Lan, Daoliang; Li, Jian; Yang, Lixue; Xiong, Xianrong (Frontiers in Veterinary Science, 2025)
IntroductionSemen cryopreservation is a crucial method for preserving genetic resources and accelerating the breeding process in domestic animals. However, the frozen-thawed process often leads to physical and chemical damage in semen, resulting in oxidative stress that diminishes sperm vitality and fertilization potential. This study aimed to explore the effects of docosahexaenoic acid (DHA) on the quality of frozen-thawed yak semen.MethodsSemen samples were collected from six healthy adult Maiwa yaks and cryopreserved in liquid nitrogen using extenders with varying DHA concentrations: 0, 0.1, 1, 10, and 100 ng/mL. After thawing, we assessed indices, antioxidant capacity, mitochondrial activity, and apoptosis status to identify the optimal DHA concentration.Results and discussionOur findings indicate that the addition of DHA significantly improved the total motility (TM), progressive motility (PM), velocity of straight line (VSL), curvilinear velocity (VCL), and average path velocity (VAP) of cryopreserved spermatozoa, as well as the integrity of membrane and acrosome (P < 0.05). Additionally, DHA supplementation markedly reduced the levels of reactive oxygen species (ROS) and malondialdehyde (MDA) in frozen-thawed yak spermatozoa (P < 0.05) and enhanced the antioxidant enzyme activities (T-AOC, SOD, CAT, GSH-Px, P < 0.05). It also improved the mitochondrial membrane potential (MMP) and ATP levels (P < 0.05). Notably, the group treated with 10 ng/mL DHA showed significantly better outcomes than the other treatment groups (P < 0.05). Furthermore, the addition of 10 ng/mL DHA to the semen cryopreservation dilution effectively decreased the apoptotic ratio of frozen-thawed yak spermatozoa (P < 0.05), and notably upregulated the expression level of anti-apoptotic protein Bcl-2 (P < 0.05), while downregulating the expression of the pro-apoptotic protein Bax and Caspase3 (P < 0.05).ConclusionIn conclusion, the incorporation of 10 ng/mL DHA into semen extenders enhances the quality and viability of yak sperm after cryopreservation by alleviating the oxidative stress, bolstering antioxidant defenses, and preserving mitochondria function, as well as inhibiting the apoptotic pathway activation.